2021
DOI: 10.1186/s13000-021-01163-7
|View full text |Cite
|
Sign up to set email alerts
|

Large cell morphology, CMYC+ tumour cells, and PD-1+ tumour cell/intense PD-L1+ cell reactions are important prognostic factors in nodal peripheral T-cell lymphomas with T follicular helper markers

Abstract: Background The clinicopathological characteristics and prognostic factors in nodal peripheral T-cell lymphomas (PTCLs) with two or more T follicular helper markers (TFH+) are not adequately investigated. Methods Immunohistologically, we selected 22 patients with TFH+ lymphoma (PTCL-TFH) in 47 of PTCL-not otherwise specified (NOS), and subclassified into large and small cell groups. We compared the two groups with 39 angioimmunoblastic T-cell lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…As CAR T cells are increasingly explored in multiple disease indications ( 55 ), a second generation anti–PD-1 CAR approach could be considered in oncology to treat selective PD-1–expressing tumors such as angioimmunoblastic T cell lymphoma ( 56 59 ) and nodal peripheral T cell lymphomas with TFH markers ( 60 ). Another application of anti–PD-1 CAR T cells could be in the treatment of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…As CAR T cells are increasingly explored in multiple disease indications ( 55 ), a second generation anti–PD-1 CAR approach could be considered in oncology to treat selective PD-1–expressing tumors such as angioimmunoblastic T cell lymphoma ( 56 59 ) and nodal peripheral T cell lymphomas with TFH markers ( 60 ). Another application of anti–PD-1 CAR T cells could be in the treatment of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 There are no large studies exclusively on the clinical characteristics of nodal PTCL with TFH phenotype (since this case was diagnosed before WHO-HAEM5 and ICC-2022 were published, we use this pathological diagnosis hereafter); however, like AITL, it is considered to be a clinically aggressive disease. [7][8][9] A few scattered case reports have reported that a subset of newly diagnosed or relapsed patients with AITL or FTCL responded to immunosuppressive therapies such as prednisolone (PSL) and/or cyclosporin A (CsA). [10][11][12][13] However, to the best of our knowledge, there are no reports on patients with nodal PTCL with TFH phenotype who responded to immunosuppressive therapies.…”
Section: Introductionmentioning
confidence: 99%